(untitled) (Jóvenes en la Ciencia, 2025)
Plastics have revolutionized modern life, but their accumulation in different ecosystems has generated a global pollution crisis driven by our reliance on, and demand for low-cost, disposable materials. The biodegradation of plastic polymers by fungi, using enzymes that biodegrade them, is a challenging but attractive and environmentally friendly option. In this regard, a fungal consortium capable of growing on polyethylene terephthalate (PET) was previously obtained, and the growth of one of the fungal isolates (C2) was characterized on various cellulosic and plastic polymers as the sole carbon source. The results indicate differential growth in different culture media, highlighting its optimal growth in MEA liquid medium at pH 5.5 and in PDA solid medium at pH 5.6, where it achieved the greatest radial growth and presented distinctive morphological characteristics. During its cultivation in MMMs supplemented with different carbon sources (cellulosic or plastic polymers), enzymatic activities such as β-glucosidase, cellobiosidase, and esterase were induced, which are secreted into the culture medium depending on the polymer used as a carbon source. Identifying optimal growth conditions represents a key step in characterizing the fungus and validating its potential use as a biodegrading agent in polymer-contaminated environments. These results suggest that C2 is viable for further studies focused on the biodegradation of cellulosic polymers and plastics, strengthening its potential application in environmental improvement processes.